Analysis of growth and exploitation rate of Muraenesox cinerus in the Bengkalis Waters, BengkalisRegency - Dian Sufitri; Eni Sumiarsih; Adriman Adriman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
Abstract Malong fish (Muraenesox cinerus) is a demersal fish that has important economic value and provides large contribution in the number of fish catches in the Bengkalis Regency. The purpose of this research is to find out the growth and exploitation rate the fish in the Bengkalis waters. This research was conducted in May-July 2020 and fish samples were collected from the fish landing place located in the Meskom Village. Data were analysis by aELEFAN I method (Electronic Lenght Frequencys Assesment Tool) from the FISAT II (FAO-ICLARM Fish Stock Assesment Tool) software. Muraenesox cinerus captured were 82 samples consisted of 34 males and 48 females. The length frequency distribution of the female fish shown that the most common fish were around 149-161 cm TL, while that of the males were 142-153 cm TL. The length-weight relationship of male was negative allometric and female was negative allometric. The growth coefficient (K) of the male fish was 10/year while that of the female was 5.01/year, the infinitive length (L∞) of male was 201 cm and that of the female was 213 cm. The theoretical lifespan (t0) of male was -0.0086/year while that of the female was -0.0174/year. The Von Bertalanffy growth equation of the male was Lt=201(1-e-10(t+0.0086)) and that of the female was Lt=213(1-e-5.01(t+0.0174)). The estimated natural mortality (M) of the female was 2.94/year, the mortality due to catching activity (F) was 4.51/year. The suspected natural mortality (M) of the male was 4.70/year, the mortality due to catching activity (F) was 20.26/year. The exploitation rate (E) of the male was 81% and that of the female was 61% or already exceeds the optimum exploitation value limit of 50%.Keywords: Exploitation Rate, Growth Pattern, Long-Weight relationship, Mortality, Silver conger, Von Bertalanffy